Scott Volkers exercise routine for core body strength, mobility and flexibility - Volkers, S.
The exercises presented are just a few of the available ones, which have been collected of a number of years from various sources around the world. These exercises were added together to then form a routine which begins with stretching and mobilizing and then moves through stabilizing and cross body strengthening. This routine can be used daily or slotted in anywhere into a swimmers program. Its benefits can be enormous and can transform a weak and unstable person into a well-coordinated, strong and athletic one.